Financial Impact of Surgical Wound Infection Post Elective Sectio Caesaria in Hospital - Noveyla hardhaning tyas; Nurhayati, Mafizatun (Adpebi International Journal of Multidisciplinary Sciences, 2022)
Purpose –The hospital is responsible for patient safety during the treatment period. Surgical wound infection is part of the main problem in midwifery services because it can hinder surgical wound healing, increase treatment time and increase treatment costs. As well as increasing the morbidity and mortality rates in obstetric services. The aim of this study was to determine the effect of surgical wound infection on patient care costs. Methodology/approach –The research method used by the researcher is a qualitative approach with a descriptive method. The results showed that post-cesarean surgical wound infection had an impact on finances, namely the high cost of hospital care. This is in accordance with the results of interviews and documentation conducted by researchers. Findings –It was concluded that postoperative wound infection elective caesarean section increased hospital costs. Large annual cost savings can be achieved by reducing the incidence of surgical site infections.